Bovine Trichomonosis in Cattle: Trends in diagnostic approaches - Challenges and Opportunities - Geethanjali, Karli (International Journal of Scientific Research in Biological Sciences, 2025)
Bovine Trichomonosis is a most neglected venereal diseases of cattle that causes severe reproductive failure. With current understanding, early disease detection and keeping diseased animals in confinement are the only viable strategies. There have also been several reports of zoonotic transmission in immunocompromised humans. According to World Organization of Animal Health recommendations, few culture and RT-PCR techniques for detecting Trichomonas foetus parasites in clinical samples have been established. Testing could not be expanded to regular screening and point-of-care settings due to a scarcity of testing kits, greater prices, and longer turnaround times. This article provides the trends in development of various diagnostic methods and their applicability. Furthermore this review highlights the limitations of the current methods and proposes the development of easy to use serological testing devices like Indirect ELISA (iELISA) and Lateral Flow Assay (LFA) rapid kit as Point of care testing (POCT) assays that are suitable for effective implementation of screening and monitoring of disease progress in herds.